Disentangling inflammatory from fibrotic disease activity by fibroblast activation protein imaging. Issue 11 (21st July 2020) - Schmidkonz, Christian; Rauber, Simon; Atzinger, Armin; Agarwal, Rahul; Götz, Theresa Ida; Soare, Alina; Cordes, Michael; Prante, Olaf; Bergmann, Christina; Kleyer, Arnd; Ritt, Philipp; Maschauer, Simone; et al.
Abstract : Objectives: To date, there is no valuable tool to assess fibrotic disease activity in humans in vivo in a non-invasive way. This study aims to uncouple inflammatory from fibrotic disease activity in fibroinflammatory diseases such as IgG4 -related disease. Methods: In this cross-sectional clinical study, 27 patients with inflammatory, fibrotic and overlapping manifestations of IgG4 -related disease underwent positron emission tomography (PET) scanning with tracers specific for fibroblast activation protein (FAP; 68 Ga-FAP inhibitor (FAPI)-04), 18 F-fluorodeoxyglucose (FDG), MRI and histopathological assessment. In a longitudinal approach, 18 F-FDG and 68 Ga-FAPI-04 PET/CT data were evaluated before and after immunosuppressive treatment and correlated to clinical and MRI data. Results: Using combination of 68 Ga-FAPI-04 and 18 F-FDG-PET, we demonstrate that non-invasive functional tracking of IgG4 -related disease evolution from inflammatory towards a fibrotic outcome becomes feasible. 18 F-FDG-PET positive lesions showed dense lymphoplasmacytic infiltration of IgG4 + cells in histology, while 68 Ga-FAPI-04 PET positive lesions showed abundant activated fibroblasts expressing FAP according to results from RNA-sequencing of activated fibroblasts. The responsiveness of fibrotic lesions to anti-inflammatory treatment was far less pronounced than that of inflammatory lesions. Conclusion: FAP-specific PET/CT permits the discrimination between inflammatory and fibrotic activity in IgG4 -related disease. This finding may profoundly change the management of certain forms of immune-mediated disease, such as IgG4 -related disease, as subtypes dominated by fibrosis may require different approaches to control disease progression, for example, specific antifibrotic agents rather than broad spectrum anti-inflammatory treatments such as glucocorticoids.